Radiation with concurrent radiosensitizing capecitabine tablets and single-dose mitomycin-C for muscle-invasive bladder cancer: A convenient alternative to 5-fluorouracil. (September 2020) - Voskuilen, Charlotte S.; van de Kamp, Maaike W.; Schuring, Nannet; Mertens, Laura S.; Noordzij, Arjen; Pos, Floris; van Rhijn, Bas W.G.; van der Heijden, Michiel S.; Schaake, Eva E.
Highlights: Chemoradiation is a bladder-sparing treatment in selected bladder cancer patients. This is the first study evaluating chemoradiation with capecitabine tablets in bladder cancer. Two-year local disease-free survival was 79% and acute grade 3–4 toxicities occurred in 10% of patients. This suggests that capecitabine is a reasonable alternative to 5-FU, with the advantage of oral administration and possibly less toxicity. Abstract: Background and purpose: Chemoradiation (CRT) with mitomycin-C (MMC) and 5-fluorouracil (5-FU) has been shown to be superior to radiation alone in patients with muscle-invasive bladder cancer (MIBC). MMC/capecitabine is an effective replacement for 5FU as a radiosensitizer in other malignancies but has not been studied in bladder cancer. We evaluated the outcomes of MIBC patients treated with concurrent radiation and MMC/capecitabine. Materials and methods: MIBC patients treated with CRT (60 Gy in 5 weeks with single-dose MMC and capecitabine orally twice daily) between 2014 and 2019 were identified. Acute (<90 days) and late toxicity were registered. Endpoints were clinical complete response (cCR) in the bladder assessed by cystoscopy 3 months after CRT, locoregional disease-free survival (LDFS) and the number of salvage cystectomies. Results: We analysed 71 cT2-4aN0-2 M0 MIBC patients (median age 70 years). Twenty-one (30%) patients received neoadjuvant or induction chemotherapy and 14 (20%) patients underwent a pelvic lymph node dissection prior to CRT. All patients received the full dose of planned radiation. Seven (10%) patients experienced acute grade 3–4 toxicities and 2 (3%) patients experienced late grade 3–4 toxicities. Sixty-eight (96%) patients achieved cCR. Eight (11%) patients had a bladder recurrence, of whom 3 (4%) required salvage cystectomy. Two-year LDFS was 79% (95% CI: 68–88) at a median follow-up of 23 (95% CI: 17–28) months. Conclusion: Radiation with concurrent MMC/capecitabine is a well-tolerated bladder-sparing treatment. Severe toxicity is infrequent and locoregional tumor control and short-term disease free survival appear similar to previous studies with MMC/5FU.